Honey bee promoter sequences for targeted gene expression. Issue 4 (14th May 2013) - Schulte, C.; Leboulle, G.; Otte, M.; Grünewald, B.; Gehne, N.; Beye, M.
Abstract The honey bee, Apis mellifera, displays a rich behavioural repertoire, social organization and caste differentiation, and has an interesting mode of sex determination, but we still know little about its underlying genetic programs. We lack stable transgenic tools in honey bees that would allow genetic control of gene activity in stable transgenic lines. As an initial step towards a transgenic method, we identified promoter sequences in the honey bee that can drive constitutive, tissue‐specific and cold shock‐induced gene expression. We identified the promoter sequences of Am‐actin5c, elp2l, Am‐hsp83 and Am‐hsp70 and showed that, except for the elp2l sequence, the identified sequences were able to drive reporter gene expression in Sf21 cells. We further demonstrated through electroporation experiments that the putative neuron‐specific elp2l promoter sequence can direct gene expression in the honey bee brain. The identification of these promoter sequences is an important initial step in studying the function of genes with transgenic experiments in the honey bee, an organism with a rich set of interesting phenotypes.